Towards practice-based professional development by teacher educators: Perspectives from self-study research in Eritrea - Idris, Khalid Mohammed; Kálmán, Anikó (Nordic Journal of Comparative and International Education (NJCIE), 2023)
Teacher education reform has advocated the implementation of widely espoused pedagogic changes in many contexts, particularly in Sub-Saharan African countries. This paper focused on the central agents in the reform process, i.e., teacher educators. Framed within the emerging conceptualizations of practice-based professional development of teacher educators, the study explores perspectives for improving educators’ teaching based on the self-study experiences of the first author while supporting the reflective practices of a group of student teachers in Eritrea. Self-study methods and tools including interactive discussions among colleague educators and critical friends, journaling, and course artifacts were used while developing the findings. The findings identified the dynamics of how researching situated concerns of teaching and learning frames problems of practice and also invokes sources and situations for developing motivations of educators in maintaining inquiry and improvement stances. We argue that such a dynamic is critical in productively engaging with teacher educators' professional learning in practice in similar contexts.